Quadro Editorial (Estudos em Design, 2021)
EditoresCristina PortugalRita Maria de Souza CoutoAvaliadores desta edição v. 29, n. 1 (2021)Adriana GralowAlexandre FarbiarzAlexandre Santos de Oliveira Aline Eyng SaviÁlvaro José Barbosa SousaAna Veronica PazminoAndré Ribeiro de OliveiraAngélica AdverseAntônio Ferreira Colchete FilhoBeany MonteiroCássia Letícia CarraraCarlo FranzatoClice MazzilliClaudio SilvaCristina PortugalCyntia Santos MalagutiDaniel RaposoDaniela AlvesDanielly Amatte LopesDoris KosminskyEdson Rufino de SouzaEloiza Andrade CorrêaEverton da SilvaFernanda CardosoFernanda HenriquesFernando Fogliano Frederico Braida Gabriel PatrocínioGuilherme Englert Corrêa MeyerHugo Sant'AnnaIone Maria Ghislene BentzJoao Eduardo chagas SobralJoana QuentalKando FukushimaKátia Carvalhaes PêgoLeticia Affini Letícia Pedruzzi Fonseca Luciane FadelLuiz AgnerLuiza Falcão Soares CunhaLuiza NovaesMárcio GuimarãesMarcos BragaMaria Cristina IbarraMaria José Jorente Mariana Cantisani PaduMariano Lopes de Andrade NetoMaristela Mitsuko OnoMonica TavaresOtniel Josafat López AltamiranoPaula Piva LinkeRafael EfremRafaella PeresRaimundo Lopes DinizRanielder Fábio de FreitasRaquel NoronhaRavi PassosRicardo Cunha LimaRogério José CâmaraRomero ToriRosimeri Franck PichlerSandra SouzaSérgio Luciano da SilvaTiago Barros Pontes SilvaVera DamazioVirginia Tiradentes SoutoViviane NunesWagner BandeiraWalter Correia